Optimisme dalam Lirik Lagu Waka-Waka dan Tahayya (Soundtrack Piala Dunia): Kajian Sastra Banding - 'Aini, Zahratul; Tasnimah, Tatik Mariyatut (Diwan: Jurnal Bahasa dan Sastra Arab, 2023)
The FIFA World Cup is a prestigious football competition held every four years in a different country. The twenty-second world cup in 2022 will be held in Qatar. To enliven the competition, works of various forms emerged as participation that implied a message. The songs Waka-Waka (This Time for Africa) and Tahayya became the soundtrack of the World Cup held in South Africa and Qatar. In this study, researchers sought to uncover the concept of Optimism from two song lyrics from different countries and languages. The method used by the author in this research is descriptive and comparative method. The results showed a difference in the concept of Optimism in the two songs studied, the lyrics of the song Waka-Waka (This Time for Africa) imply the concept of Optimism that can be achieved individually without including elements of religion and solidarity in contrast to the lyrics of the song Tahayya which conveys religious messages as the basis for optimism.